ANALISIS JUMLAH CEMARAN MIKROBA DAN IDENTIFIKASI SALMONELLA sp. DAN VIBRIO CHOLERAE PADA IKAN TONGKOL DIBEBERAPA TEMPAT PEMASARAN WILAYAH KOTA KUPANG - Barelinda, Maria G.; Picauly, Intje; Aspatria, Utma (Pergizi Pangan DPD NTT, 2011)
Fish as a food substance is a valuable and prospective source of nutrition. Thus, fish can easily spoil if contaminated by microbe and may cause food borne diseases if contaminated by pathogen such as Salmonella sp and Vibrio cholera. This research generally aims to analyze the number of soiled microbe in several marketing places in Kupang city. Meanwhile, the specific aims are to (1) analyze the number of soiled microbe in several marketing places in Kupang city, (2) find out the correlation between marketing places and number of soiled microbe, (3) identify Salmonella sp bacteria in Tongkol fish sale in several marketing places in Kupang city, and (4) identify Vibrio cholera bacteria in Tongkol fish sale in several marketing places in Kupang city. Method used in this research is Laboratory Experiment using complete damp design with 3 treatment (Tongkol fish from Oeba market, Pasir Panjang market and fish peddle) and 2 retests.